TB4093 BIOENERGY AND CHEMICAL ENGINEERING RESEARCH II STUDY OF BIOGAS POTENTIAL FROM FERMENTED CASSAVA FLOUR (FERCAF) WASTEWATER WITH SIMULATION USING ASPEN PLUS - Destrio Saputra, Rocky
In the manufacture of fercaf (fermented cassava flour), waste will be produced, especially wastewater obtained from the washing process and the fermentation process at the factory for making fermented flour. Unprocessed wastewater can pollute the environment. The wastewater of the fercaf manufacturing plant will naturally decompose because it has a high content of organic materials. The wastewater of the fercaf manufacturing plant can be processed through anaerobic digestion processes to produce biogas. Making biogas from waste can reduce the impact of waste pollution on the environment, and can help create energy sovereignty because the biogas produced can be used by factories or used by the general public around the fercaf manufacturing plant. The research conducted will focus on simulating the manufacture of biogas from fercaf wastewater using the aspen plus application to determine the potential for biogas that can be produced from fercaf wastewater. The simulation was built based on four stages of biogas production, namely the stages of hydrolysis, acidogenesis, acetogenesis and methanogenesis. The model was built by simulating the biogas production process from tapioca liquid waste first, the data on the amount of biogas produced from the simulation model using the Aspen Plus application was compared with the amount of biogas generated from the literature data, this aims to validate the model built. The amount of biogas produced from the simulation of the biogas production process from tapioca flour wastewater gave a relatively close biogas yield to the amount of biogas produced from literature data. The simulation model can be used to simulate the biogas production process from fercaf wastewater. The amount of biogas produced from 1 m3 of fercaf liquid waste is predicted to be 1.754 m3/day consisting of 56.75% CH4, 26.52% CO2, 16.73% other gases. This data can be taken into consideration by a fercaf plant before implementing a biogas system.